Thrombolytic potential in bacteria isolated from fermented durian tempoyak - CHRISTY PRISKILA; VALERIE VIDIAN; ASTIA SANJAYA; MARCELIA SUGATA; REINHARD PINONTOAN (Society for Indonesian Biodiversity, 2022)
Abstract. Priskila C, Vidian V, Sanjaya A, Sugata M, Pinontoan R. 2022. Thrombolytic potential in bacteria isolated from fermented durian tempoyak. Biodiversitas 23: 5731-5737. Cardiovascular disease is one of the leading causes of death worldwide and is primarily caused by dysregulation in the blood clotting system leading to the formation of unwanted blood clots (thrombi). Thrombolytic therapy, which aims to break down unwanted blood clots, employs various agents possessing thrombolytic activity. However, the harmful side effects of conventional thrombolytic agents necessitate the exploration of new and safer agents with high thrombolytic activities. Thrombolytic agents can be obtained from various sources, including fermented foods. Tempoyak is a condiment made from fermented durian, which is found in some regions of Indonesia, and is reported to contain beneficial microorganisms. The aim of this study was to isolate and identify thrombolytic agents from tempoyak. After several pure microbial colonies were successfully isolated from tempoyak, they were screened for proteolytic activity on skim milk agar medium. The isolated colonies with proteolytic activity were then subjected to several tests, including the whole blood clot lysis test, euglobulin clot lysis test, fibrin plate method, and zymography. Subsequently, the isolates with thrombolytic and fibrinolytic activity potential were identified in terms of their morphology and biochemistry. In this study, three bacteria with thrombolytic activity potential were successfully isolated. Fibrin zymography indicated that the molecular weights of the proteins that play roles in the fibrinolytic activity ranged from approximately 30 to 153 kDa, which were suspected to correspond to serine protease, cysteine protease, and/or metalloprotease. All three isolates were identified as belonging to the genus Corynebacterium. This is the first report discussing the thrombolytic and fibrinolytic activities of Corynebacterium sp. derived from fermented food.